The Asymptotic Behavior of the Time Fractional Schrödinger Equation on Hilbert Space - Prado-Castillo, H (American Institute of Physics, 2020)
The purpose of this article is to show the asymptotic behavior of the solution of the abstract Schrödinger equation with time fractional derivative of order α ∈ (0, 1). We give a detailed description of the long time behavior of the corresponding operator solution. As it is expected in this case, the dynamics are not governed neither by a group nor by a semigroup. © 2020 Author(s).